Global 3D full-scale turbulence simulations of TCV-X21 experiments with SOLEDGE3X - H. Bufferand; G. Ciraolo; R. Düll; G. Falchetto; N. Fedorczak; Y. Marandet; V. Quadri; M. Raghunathan; N. Rivals; F. Schwander; E. Serre; S. Sureshkumar; et al. (Nuclear Materials and Energy)
First principle modelling of edge plasma turbulence including neutrals and plasma recycling on the wall remains a challenge, in particular due to the long time scales necessary to simulate to reach particle balance. In this contribution, we propose a strategy to address these long time scales with the fluid code SOLEDGE, resorting to 2D reduced models for turbulence as well as 3D coarse grid simulations. The approach is applied to simulate TCV-X21 reference plasma scenario for edge turbulence modelling validation.